Von Hippel-Lindau Disease (VHL): A need for a murine model with retinal hemangioblastoma - Park, Stanley (2012)
Von Hippel-Lindau (VHL) disease is a highly penetrant autosomal dominant systemic malignancy that gives rise to cystic and highly vascularized tumors in a constellation of organs. Patients with VHL disease commonly present with hemangioblastomas in the central nervous system and the eye while other manifestations include pheochromocytoma, clear cell renal cell carcinoma, endolymphatic sac tumors of the middle ear, pancreatic cystadenomas, epididymal and broad ligament cystadenomas. Animal models inactivating the VHL gene product in various organ tissues have been constructed over the past 15 years to parse its HIF-associated mechanisms and its link to tumorigenesis. These models, despite advancing our understanding the molecular role of VHL, are by and large unable to recapitulate the more common features of human VHL disease. Up to date, no model exists that develop retinal hemangioblastomas, the most common clinical manifestation. The purpose of this review is: (1) to discuss the need for an ocular VHL model, (2) to review the animal models that recapitulate clinical VHL disease and (3) to propose potential mechanisms of tumorigenesis for the development of ocular VHL.